Treatment with the senolytics dasatinib/quercetin reduces SARS‐CoV‐2‐related mortality in mice. Issue 3 (26th January 2023) - Pastor‐Fernández, Andrés; Bertos, Antonio R.; Sierra‐Ramírez, Arantzazu; del Moral‐Salmoral, Javier; Merino, Javier; de Ávila, Ana I.; Olagüe, Cristina; Villares, Ricardo; González‐Aseguinolaza, Gloria; Rodríguez, María Ángeles; Fresno, Manuel; Gironés, Nuria; et al.
Abstract: The enormous societal impact of the ongoing COVID‐19 pandemic has been particularly harsh for some social groups, such as the elderly. Recently, it has been suggested that senescent cells could play a central role in pathogenesis by exacerbating the pro‐inflammatory immune response against SARS‐CoV‐2. Therefore, the selective clearance of senescent cells by senolytic drugs may be useful as a therapy to ameliorate the symptoms of COVID‐19 in some cases. Using the established COVID‐19 murine model K18‐hACE2, we demonstrated that a combination of the senolytics dasatinib and quercetin (D/Q) significantly reduced SARS‐CoV‐2‐related mortality, delayed its onset, and reduced the number of other clinical symptoms. The increase in senescent markers that we detected in the lungs in response to SARS‐CoV‐2 may be related to the post‐COVID‐19 sequelae described to date. These results place senescent cells as central targets for the treatment of COVID‐19, and make D/Q a new and promising therapeutic tool. Abstract : New treatments are necessary to reduce the social impact of COVID‐19. Using the murine model K18‐hACE2, we demonstrated that senolytics (D/Q) reduced SARS‐CoV‐2‐related mortality, delayed its onset, and reduced the number of other clinical symptoms.